2016
DOI: 10.1016/j.vph.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

MnTBAP increases BMPR-II expression in endothelial cells and attenuates vascular inflammation

Abstract: Aims The endothelium plays an important role during vascular inflammation. Previous data have demonstrated a high expression level of manganese-superoxide dismutase (MnSOD) in endothelial cells and suggested an important role of MnSOD in several cardiovascular diseases. Manganese (III) tetrakis (4-benzoic acid) porphyrin (MnTBAP) has been shown to mimic some of the effects of MnSOD and prevented the development of diabetes and obesity. However, its effect on vascular inflammation and the underlying mechanism i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…We have shown that even in the presence of CHX, MnTBAP increases BMPR2 levels in PAECs. This goes in line with our previous findings, where pre-treatment of HUVECs with MnTBAP for 16 h prior to addition of CHX increased BMPR2 stability [25]. In summary, our data suggest that MnTBAP modulates BMPR2 degradation and underlines the role of such compound as a favorable PAH treatment.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We have shown that even in the presence of CHX, MnTBAP increases BMPR2 levels in PAECs. This goes in line with our previous findings, where pre-treatment of HUVECs with MnTBAP for 16 h prior to addition of CHX increased BMPR2 stability [25]. In summary, our data suggest that MnTBAP modulates BMPR2 degradation and underlines the role of such compound as a favorable PAH treatment.…”
Section: Discussionsupporting
confidence: 93%
“…As expected, BMPR2 levels were significantly increased after BafA1 treatment [12] ( Figure 1A). Consistent with our previous findings [25], MnTBAP treatment resulted in a dose-depndent increase of BMPR2 protein levels in PAECs ( Figure 1A or B). No significant differences on BMPR2 mRNA levels were observed after MnTBAP treatment, indicating no changes at the transcriptional level ( Figure 1C).…”
Section: Mntbap Increases Bmpr2 Levels In Vitro By Inhibiting Autophagysupporting
confidence: 93%
See 1 more Smart Citation
“…Several studies indicated that Mn supplementation could reduce high glucose-induced monocyte adhesion to endothelial cells and endothelial dysfunction and also lower blood levels of ICAM-1 and cholesterol [ 48 , 49 ], elicit anti-inflammatory effects in endothelial cells [ 100 ], and potentially prevent or delay the progression of atherosclerosis. Little is known about the Mn concentration in atherosclerosis patient samples.…”
Section: Mn and Atherosclerosismentioning
confidence: 99%
“…6 and 7). While a fair amount of data exist on the ability of MnTBAP 3to reduce normal tissue injuries (9,12,53,61,64), this MnP may not have the potential as an anticancer therapeutic.…”
Section: Redox Properties Of Mn Complexes Control Their Anticancer Efmentioning
confidence: 99%